2022
DOI: 10.21876/rcshci.v12i2.1270
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with adherence to pharmacological treatment in hypertensive patients enrolled in the HIPERDIA program

Abstract: Objective: To assess adherence to antihypertensive treatment in patients at a Family Health Strategy (FHS) unit. Methods: quantitative, transversal, and observational study with 131 hypertensive patients registered in the HIPERDIA program of an FHS located in the city of Lagarto, Sergipe, Brazil, through the analysis of medical records and the application of structured questionnaires. The assessment of the degree of adherence was carried out through the Brief Medication Questionnaire. Results: Factors related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…By implementing lifestyle modifications, patients can have a significant impact on their blood pressure control and overall health [2]. Studies have shown that patients with HTN are least educated about normal blood pressure (BP) values and lifestyle modifications required for treatment [3].…”
Section: Introductionmentioning
confidence: 99%
“…By implementing lifestyle modifications, patients can have a significant impact on their blood pressure control and overall health [2]. Studies have shown that patients with HTN are least educated about normal blood pressure (BP) values and lifestyle modifications required for treatment [3].…”
Section: Introductionmentioning
confidence: 99%